Interfacial tension, wettability, foam and emulsification properties of mono- and di-tetrapropylene diphenyl ether disulfonates. Issue 10 (3rd October 2018) - Bai, Long; Liu, Xiaochen; Jiao, Tiliu; Huo, Yueqing; Niu, Jinping
ABSTRACT: The interfacial tension, wettability, foam and emulsification properties of di-tetrapropylene diphenyl ether disulfonates (C12 -DADS) gemini-type surfactant have been studied and compared to mono-tetrapropylene diphenyl ether disulfonates (C12 -MADS) and tetrapropylene benzene sulfonates (C12 -BAS). The results show that the C12 -DADS have a lower interfacial activity compared to that of C12 -MADS and C12 -BAS. The wettability of the three surfactants decreases in the order C12 -BAS > C12 -DADS > C12 -MADS. For foam properties, the foamability and foam stability of C12 -MADS and C12 -DADS is lower than that of C12 -BAS. In addition, the emulsification ability increase in the order C12 -DADS < C12 -MADS < C12 -BAS. GRAPHICAL ABSTRACT: